Fundamental of Entrepreneurship ENT300 : Kaby Badminton Court / Abang Nasiruddin Abang Mohd Khalid ... [et al.] - Abang Mohd Khalid, Abang Nasiruddin; Abu Bakar, Abdul Rahman; Yunus, Ammar Zaqwan Aizzad; Ayup, Nurzirah (2011)
The name of our company is KABY Badminton Court. The business is in form of enterprise which consists of four members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is badminton court service which our concepts are healthy and active. Our business operation is at 2 p.m to 1 a.m on weekdays, 11 a.m to 1 a.m on weekends and close during public holiday.There are no sleeping partners and all are entitled to participate in the business management. We agreed that Abang Nasiruddin Bin Abang Mohd Khalid is our General Manager and Financial Manager, Abdul Rahman Bin Abu Bakar is the Administration Manager, Ammar Zaqwan Aizzad Bin Yunus is the Operation Manager, and Nurzirah Binti Ayup as Marketing Manager. The selection of General Manager is based on consensus among all the partners and selected based on the experience, skills and ability.